Cobalt Compounds and Applications 2019
DOI: 10.5772/intechopen.86260
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite-Type Lanthanum Cobaltite LaCoO3: Aspects of Processing Route toward Practical Applications

Abstract: Lanthanum cobaltite (LaCoO 3) perovskite-type oxide is an important conductive ceramic material finding a broad range of technical applications. Physical and chemical properties of the final lanthanum cobalt oxide powder material obtained are strongly dependent on the method of preparation. Taking in account these considerations, we focus our investigation on the solid state reaction process. The characterization of prepared lanthanum cobalt oxide material was studied by using X-ray diffractometry (XRD), scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Figure e indicates 2D pCN nanosheets having distinct flaked structures as a result of the sonicating treatment. Figure f displays FE-SEM images of LaCoO 3 having a larger and less agglomerated rhombohedral structure Figure g shows TiO 2 -grown Ti 3 C 2 sheets dispersed by LaCoO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure e indicates 2D pCN nanosheets having distinct flaked structures as a result of the sonicating treatment. Figure f displays FE-SEM images of LaCoO 3 having a larger and less agglomerated rhombohedral structure Figure g shows TiO 2 -grown Ti 3 C 2 sheets dispersed by LaCoO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we showed that single-phase perovskite LaCoO3 powders are readily obtained from lanthanum and cobalt oxide precursors by one-step solid-state synthesis at 1000 C for 8 h [44,45]. The crystal structure of LaCoO3 is rhombohedral (space group R3c, ICSD 01-084-0845).…”
Section: Resultsmentioning
confidence: 99%
“…LaCoO 3 (LCO), a complexing oxide with a perovskite-type structure, is another promising cathode material for SOFC due to its high electronic and ionic conductivities. [5,74] This mixed conductivity is attributed to the reaction sites available at the surface of LCO along with TPB without aiding any conductive materials. However, the incompatibility of this oxide with SOFC applications arises due to its high thermal expansion coefficient (TEC) and its tendency to react strongly with yttrium-stabilized zirconia electrolyte at temperatures exceeding 900 °C.…”
Section: Lscf (La 1-x Sr X Co 1-y Fe Y O 3-δ ) Cathode Materialsmentioning
confidence: 99%